2010
DOI: 10.1016/j.esas.2010.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Presacral retroperitoneal approach to axial lumbar interbody fusion: a new, minimally invasive technique at L5-S1: Clinical outcomes, complications, and fusion rates in 50 patients at 1-year follow-up

Abstract: BackgroundThe presacral retroperitoneal approach to an axial lumbar interbody fusion (ALIF) is a percutaneous, minimally invasive technique for interbody fusion at L5-S1 that has not been extensively studied, particularly with respect to long-term outcomes.ObjectiveThe authors describe clinical and radiographic outcomes at 1-year follow-up for 50 consecutive patients who underwent the presacral ALIF.MethodsOur patients included 24 males and 26 females who underwent the presacral ALIF procedure for interbody fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…1A). 4,12,[17][18][19][20]22 Similarly, the fusion rates for AxiaLIF and ALIF are also comparable and range from 88% to 100% (see Fig. 1B).…”
Section: Results From Open Fusion Proceduresmentioning
confidence: 86%
See 4 more Smart Citations
“…1A). 4,12,[17][18][19][20]22 Similarly, the fusion rates for AxiaLIF and ALIF are also comparable and range from 88% to 100% (see Fig. 1B).…”
Section: Results From Open Fusion Proceduresmentioning
confidence: 86%
“…In 2010, Bohinski et al 12 reported clinical outcomes and fusion rates on 50 AxiaLIF patients with an 1-year follow-up.…”
Section: Results From Axialif Studiesmentioning
confidence: 98%
See 3 more Smart Citations